A prodrug strategy for the oral delivery of a poorly soluble HCV NS5B thumb pocket 1 polymerase inhibitor using self-emulsifying drug delivery systems (SEDDS). Issue 2 (15th January 2015) - Beaulieu, Pierre L.; De Marte, Josie; Garneau, Michel; Luo, Laibin; Stammers, Timothy; Telang, Chitra; Wernic, Dominik; Kukolj, George; Duan, Jianmin
Graphical abstract: Abstract: A prodrug approach was developed to address the low oral bioavailability of a poorly soluble (<0.1 μg/mL in pH 6.8 buffer) but highly permeable thumb pocket 1 HCV NS5B polymerase inhibitor. Bioconversion rates of structurally diverse prodrug derivatives were evaluated in a panel of in vitro assays using microsomes, from either liver or intestinal tissues, simulated intestinal fluids, simulated gastric fluids or plasma. In vivo bioconversion of promising candidates was evaluated following oral administration to rats. The most successful strategy involved modification of the parent drug carboxylic acid moiety to glycolic amide esters which improved solubility in lipid-based self-emulsifying drug delivery systems (SEDDS). Crystalline prodrug analog36 (mp 161 °C) showed good solubility in individual SEDDS components (up to 80 mg/mL) compared to parent2 (<3 mg/mL; mp 267 °C) and cross-species bioconversions which correlated with in vitro stability in liver microsomes.